Development and Characterization of New Peptidomimetic Inhibitors of the West Nile Virus NS2B–NS3 Protease. Issue 2 (10th January 2013) - Hammamy, M. Zouhir; Haase, Caroline; Hammami, Maya; Hilgenfeld, Rolf; Steinmetzer, Torsten
Abstract A series of new substrate analogue inhibitors of the WNV NS2B–NS3 protease containing decarboxylated arginine mimetics at the P1 position was developed. Among the various analogues, trans‐(4‐guanidino)cyclohexylmethylamide (GCMA) was identified as the most suitable P1 residue. In combination with dichloro‐substituted phenylacetyl groups at the P4 position, three inhibitors with inhibition constants of <0.2 μM were obtained. These GCMA inhibitors have a better selectivity profile than the previously described agmatine analogues, and possess negligible affinity for the trypsin‐like serine proteases thrombin, factor Xa, and matriptase. A crystal structure in complex with the WNV protease was determined for one of the most potent inhibitors, 3, 4‐dichlorophenylacetyl‐Lys‐Lys‐GCMA (Ki=0.13 μM). The inhibitor adopts a horseshoe‐like conformation, most likely due to a hydrophobic contact between the P4 phenyl ring and the P1 cyclohexyl group, which is further stabilized by an intramolecular hydrogen bond between the P1 guanidino group and the P4 carbonyl oxygen atom. These inhibitors are stable, readily accessible, and have a noncovalent binding mode. Therefore, they may serve as suitable lead structures for further development.